Bondora: another brick in the proceduralization of the consumers’ substantive rights - Santaló Goris, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Last December 2019, the Court of Justice of the European Union (“CJEU”) rendered the judgment Bondora (Joined Cases C‑453/18 and C‑494/18). In this case, the CJEU explored whether it is possible to carry out an ex officio review of the fairness of the contractual terms in the European Payment Order (“EPO”). Whereas the CJEU had already addressed similar preliminary references in the context of the domestic payment orders, for the first this issue is addressed in an European uniform proceeding. This case note aims at analysing the Bondora judgement as well as the impact the judgment had on the functioning and the structure of the EPO proceeding.
Keywords: European civil procedure; European Payment Order; CJEU judgement; consu¬mers’ protection; unfairness of the contractual terms